1975
DOI: 10.1002/dev.420080110
|View full text |Cite
|
Sign up to set email alerts
|

Arousal and temporal factors in imprinting in mallards

Abstract: A number of factors affecting the learning processes in laboratory imprinting were examined. Two factors alone explain the degree to which young ducklings learn the characteristics of a given model: the length of exposure to the model, and the endogenous arousal state of the duckling. A third, the effect of muscular exertion is not warranted.The characteristics of some models are more rapidly learned than others, and the significance of this fact for biochemical studies of learning is discussed. In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The corticosterone level in this situation would then probably be indicative of the fear induced in the birds by the exposure to the non-familiar object (e.g. Martin & Schutz 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The corticosterone level in this situation would then probably be indicative of the fear induced in the birds by the exposure to the non-familiar object (e.g. Martin & Schutz 1975).…”
Section: Discussionmentioning
confidence: 99%
“…increase in the level of arousal is important in imprinting in birds (Fischer, 1970;Kovach, 1970;Martin & Schutz, 1974). The pattern of response to both experimental odors was very similar.…”
Section: Resultsmentioning
confidence: 78%
“…The behavioural differences observed during the choice test thus probably result from unlearned preferences for one model as they already occurred during the first encounters between models and chicks. Such preferences have already been demonstrated: MARTIN and SCHUTZ (1975) for example showed that young mallard ducklings are more likely to follow and to imprint on a , blue ball than on a red cube. Detailed studies of the chicks' preferences have also been published (e.g.…”
Section: Twittersmentioning
confidence: 75%